2019
DOI: 10.1080/15459624.2019.1628966
|View full text |Cite
|
Sign up to set email alerts
|

Experience of Chicagoland acute care hospitals in preparing for Ebola virus disease, 2014–2015

Abstract: During the 2014-2015 Ebola virus disease (EVD) outbreak, hospitals in the United States selected personal protective equipment (PPE) and trained healthcare personnel (HCP) in anticipation of receiving EVD patients. To improve future preparations for high-consequence infectious diseases, it was important to understand factors that affected PPE selection and training in the context of the EVD outbreak. Semistructured interviews were conducted with HCP involved with decision-making during EVD preparations at acut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
21
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 26 publications
3
21
0
1
Order By: Relevance
“…Hands-on training in PPE was commonly used with enhanced PPE ensembles during the Ebola Virus Disease outbreak of 2014-2015, and trainees identified hands-on training as has having the greatest influence on their confidence to care for Ebola Virus Disease patients. [15] Such training could be integrated into HCWs' clinical competency skills tests. Clearly, the evidence in this and other work demonstrate that the current approaches are inadequate to obtaining the desired PPE doffing behaviors from HCWs.…”
Section: Discussionmentioning
confidence: 99%
“…Hands-on training in PPE was commonly used with enhanced PPE ensembles during the Ebola Virus Disease outbreak of 2014-2015, and trainees identified hands-on training as has having the greatest influence on their confidence to care for Ebola Virus Disease patients. [15] Such training could be integrated into HCWs' clinical competency skills tests. Clearly, the evidence in this and other work demonstrate that the current approaches are inadequate to obtaining the desired PPE doffing behaviors from HCWs.…”
Section: Discussionmentioning
confidence: 99%
“…Maintaining a skilled workforce in the use of high-level PPE is an important part of pandemic preparedness, particularly for hospitals with biocontainment capacity. Research from the USA showed that HCWs expect PAPRs to be available for them to use with EVD patients [43]. However, PAPR components are relatively expensive and the cost of maintaining an in-date stock of PAPR components between HCID events or outbreaks may be a deterrent to using them for training, especially if the risk of an actual case is very low.…”
Section: Discussionmentioning
confidence: 99%
“…This issue was apparent in the changing guidelines for PPE during the 2014-2015 EVD. 5 The risk-based approach we propose in this study enables transparent decisionmaking, even in the face of uncertainty or disagreement, because each step of the approach can be documented, allowing review (and critique) by others.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in the Chicago area, HCP used visual inspection and colored liquids (eg, Kool-Aid [The Kraft-Heinz Co]) to evaluate dermal coverage and fluid impermeability of PPE, respectively, to increase confidence in PPE selection decisions during EVD preparations. 5 Implementation of a systematic risk-based process for selection of a PPE ensemble to protect HCP from infectious diseases benefits from a team with expertise in occupational health, infectious diseases, human factors, and health care activities. The questions in Table 1 are intended to help ensure that PPE ensembles are evaluated holistically, but may not be complete.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation